Food, rural, agricultural and fisheries policies in Albania - Dashi E.; Guri F. (Les agricultures méditerranéennes : analyses par pays, 2008)
To discuss about the economic characteristics of agriculture is at the same time easy and difficult, easy because agriculture remains one of the most important activities of Albanian economy, but also difficult because by definition this sector is particular where the rules are not always the same as in the traditional economy. In Albania, traditionally we have been conscious that agriculture is not only one of the productive activities of the society, but is an important element of the socio-economic regulation. The setting up of the agriculture rules and specially a proper system must reflect the economic system established in the country, but in Albania those characteristics have been much more pointed. On these conditions to study the agricultural characteristics of the country, we should take into consideration also the history, economy and social development. In this article we tend to explain the actual situation of the agriculture and the perspectives from the economic point of view.